Evaluate the function at the indicated values. (If an answer is undefined, enter

Algebra
Tutor: None Selected Time limit: 1 Day

f(x) = 6x2 + 2x − 12

f(0)      =          

f(2)      =          

f(−2)    =          

f(2)      =          

f(x + 1)            =          

f(−x)    =         

Feb 9th, 2015

f(x) = 6x2 + 2x − 12

f(0)  =    6*0^2 + 2*0- 12 = UNDEFINED

f(2)  =    6*2^2 + 2*2 - 12 = 24 + 4 - 12 = 16

f(−2)  =    6*(-2)^2 + 2*-2 - 12 = 24 - 4 - 12 = 8

f(2)  =    6*2^2 + 2*2 - 12 = 24 + 4 - 12 = 16

f(x + 1)  =   6*(x+1)^2 + 2*(x+1) - 12 = 6 ( x^2 + 2x + 1 ) + 2x + 2 - 12 =

6x^2 + 12x + 6 + 2x + 2 - 12 = 6x^2 + 14x - 4

f(−x)  =        6(-x)^2 + 2 ( - x ) - 12 = 6x^2 - 2x - 12


Feb 9th, 2015

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.
Click to visit
The Notebank
...
Feb 9th, 2015
...
Feb 9th, 2015
Mar 27th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer